From Diagnosis to Surgery: Analyzing Complication Rates in Surgical Procedures - Abdulsalam Mohammed Aleid; Hasan Ali Abdullah AlAidarous; Abdulwahab Ahmed Alzahrani; Yousef Khalaf A Alghamdi; Mohammed Yousef Alessa; Loai Saleh Albinsaad; Abdulrahman Almoslem; Saud Nayef Salem Aldanyowi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: From the diagnosis to the operation, Time is a crucial determinant of healthcare quality. Prolonged durations may impact therapy outcomes and cause delays. Examining the frequency of surgical complications and the time interval between diagnosis and surgery was the aim of this investigation. Methods: A total of 563 individuals who had surgery were included in this retrospective analysis. Patient demographics, operation specifics, comorbidities, complications, and the median 52.85-day time span between diagnosis and surgery were all recorded. The following complications were examined: heartburn, fever, infection, nausea, disorientation, shock, thrombosis, bleeding, discomfort, and elevated blood pressure. Chi-square testing, correlation, and Bayesian model comparison were used to examine relationships between complications and surgical time. Results: Chi-square analyses revealed no connections between any complication and the amount of time between diagnosis and operation (all p>0.05). Time to surgery had weak positive connections (r=0.041), high blood pressure (r=-0.094), and thrombosis (r=-0.052) with these factors, but weak negative associations (r=-0.019), nausea (r=-0.04), and shock (r=-0.016) with these factors and infection. Positive correlations between the delay to surgery and fever (BF=5.819), high blood pressure (BF=14.148), and thrombosis (BF=6.408) were shown to have moderate evidence (BF>10) according to Bayesian analysis. Additionally, there was moderate evidence of negative correlations with both perplexity (BF=28.507) and shock (BF=22.801). Conclusion: The duration from diagnosis to surgery and the incidence of postoperative complications were shown to have minimal or no significant correlations in this study. A longer time to surgery has been linked to higher chances of fever, hypertension, and thrombosis, but fewer risks of shock and confusion, according to some evidence from Bayesian analysis. To get a better understanding of how preoperative delays affect surgical outcomes, larger prospective studies are required.